2012
DOI: 10.1089/met.2011.0086
|View full text |Cite
|
Sign up to set email alerts
|

Hyperleptinemia and Hypoadiponectinemia in Extreme Pediatric Obesity

Abstract: Background: Adiponectin and leptin, adipokines associated with metabolic syndrome, type 2 diabetes, and cardiovascular disease, have not been well characterized in extreme pediatric obesity. Therefore, levels were compared in youth that were extremely obese (EO) to normal weight (NW), overweight (OW), and obese (OB) youth. Methods: Leptin, adiponectin, body mass index (BMI), blood pressure, fasting glucose, insulin, and lipids were obtained in 277 children and adolescents (age 13.4 -2.6 years; 152 boys). Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…Other studies have reported that severe pediatric obesity, compared with milder forms of adiposity and normal weight, is associated with higher levels of blood pressure, 9,10,12,13,15 dyslipidemia, 9,10,12,13,15 oxidative stress, 15 inflammation, 11,15,18 cardiorespiratory deconditioning (low fitness level) and poor pulmonary function, 9 clustering of cardiometabolic risk factors, 8,14 arterial stiffness, 17 increased carotid artery intima-media thickness, 11 and endothelial dysfunction/activation. 11,12,16,17 Perhaps most striking are the markedly elevated levels of inflammation that have been demonstrated in severe pediatric obesity.…”
Section: Cardiovascular Risksmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported that severe pediatric obesity, compared with milder forms of adiposity and normal weight, is associated with higher levels of blood pressure, 9,10,12,13,15 dyslipidemia, 9,10,12,13,15 oxidative stress, 15 inflammation, 11,15,18 cardiorespiratory deconditioning (low fitness level) and poor pulmonary function, 9 clustering of cardiometabolic risk factors, 8,14 arterial stiffness, 17 increased carotid artery intima-media thickness, 11 and endothelial dysfunction/activation. 11,12,16,17 Perhaps most striking are the markedly elevated levels of inflammation that have been demonstrated in severe pediatric obesity.…”
Section: Cardiovascular Risksmentioning
confidence: 99%
“…12,13,15,18,[77][78][79][80] Impaired glucose tolerance, a strong predictor of future development of T2DM in obese youth, is prevalent among children and adolescents with severe obesity. 77,78,81 In a study of >700 severely obese children of European decent, insulin resistance and insulin secretion were associated with 2-hour postprandial glucose levels.…”
Section: Metabolic Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Leptin plays an immunomodulatory role 32 and develops, in these patients, a low-grade chronic inflammation, 33 w h i c h i s a s s o c i a t e d w i t h m a c r o p h a g e infiltration into adipose tissue. This leads to increased proinflammatory cytokine levels, such as tumor necrosis factor-α, interleukin-1b, interleukin-6, and this situations contributes to insulin resistance 34 and a reduced immune and metabolic reservoir.…”
Section: Pathophysiology Of Obesity Leptin Biologymentioning
confidence: 99%
“…3 Other data further suggested that compared to overweight and obese children and adolescents, youth with severe obesity have a much more adverse cardiometabolic risk factor profiles and are more likely to develop diabetes and cardiovascular diseases at a younger age. 4,5 Inflammation and oxidative stress associated with childhood obesity appears to be central to the development of insulin resistance and atherosclerosis, and may be important in the pathogenesis of other comorbid conditions. 6 A previous study documented that obese children with upper quartiles of C-reactive protein (CRP) and oxidative stress markers were more likely to have metabolic syndrome and abnormal lipid profiles, suggesting that inflammation and oxidative stress are interrelated, and might be associated with harmful health effects.…”
mentioning
confidence: 99%